STUDY OF S235 STEEL CORROSION PROCESS IN WASTEWATER FROM THE PETROCHEMICAL INDUSTRY - CHELARU, Julieta Daniela; MUREŞAN, Liana Maria (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The aim of this study is to investigate the corrosion behavior of low carbon steel (S235) used in petrochemical industry. The corrosion process was analyzed in simulated wastewater at different values of pH and at different temperatures and also in real wastewater from the exploitation of crude oil from Transylvania, Romania. Two commercial corrosion inhibitors (Nalco 73413 (Nalco Products, USA,) and Galoryl IC20 (ArrMazz Chemicals SAS, USA) were tested at different concentrations. The corrosion behavior was investigated by electrochemical impedance spectroscopy and potentiodynamic polarization measurements. Adsorption of these inhibitors was found to obey Langmuir adsorption isotherm.